Cell Therapy Against Cerebral Stroke : Comprehensive Reviews for Translational Researches and Clinical Trials - Houkin, Kiyohiro; Abe, Koji; Kuroda, Satoshi (Springer Japan : Imprint: Springer, 2017)
This book presents comprehensive reviews for both translational research and clinical trials on cell therapy for stroke. Cerebral stroke is still a leading cause of death and disability. However, despite intensive research, few treatment options are available. The therapeutic potential of cell transplantation has been studied for various pathological conditions of the central nervous system (CNS) including traumatic brain injury, traumatic spinal cord injury, degenerative disease, demyelinating disease and ischemic stroke, as the injured neural tissue in the CNS has only a limited regenerative capacity. Recently, a growing body of evidence in this field suggests that cell transplantation holds great potential as a form of stroke therapy. The authors, who are experts in the field of neurosurgery, review and discuss optimal cell sources and various issues involved in translational research; further, they outline ongoing clinical trials in Japan.
Keywords: Medicine.; Neurology.; Neurosurgery.; Regenerative medicine.; Tissue engineering.; elektronické knihy; electronic books